Degradation of the insecticides fipronil and cypermethrin in green onions (Allium fistulosum) and mustard greens (Brassica juncea) - Dang Giang Chau Nguyen; Thi Lan Anh Tran; Thi Thanh Lam Tran; Thi My Duyen Ngo; Thai Long Hoang; Van Hop Nguyen; Kurt Kalcher (Vietnam Journal of Science, Technology and Engineering, 2021)
Pesticide dissipation on foods like vegetables, fruits, and cereals is one of the most concerning aspects in pesticide toxicology as it involves risks to human health and food safety. In light if this, a laboratory-scale study was conducted for two separate systems, green onions (Allium fistulosum) and mustard greens (Brassica juncea), in order to identify the dissipation of fipronil and cypermethrin, two commonly used insecticides, under a tropical climate. After the pesticide application, vegetable samples from these microcosms were collected each day for 7 days to measure fipronil and cypermethrin (n=3) residues. The analytical method was validated and showed repeatability and trueness. The decay equations fit well to first-order kinetics with a correlation coefficient of R2>0.93 and p<0.0005. The calculated half-life values of fipronil were 2.9 d for green onions and 3.2 d for mustard greens while those of cypermethrin were, respectively, 4.5 d and 3.2 d. To meet the maximum residue levels (MRL) of fipronil (0.02 mg/kg) and cypermethrin (0.7 mg/kg) on vegetables, the estimated preharvest intervals should be updated to 23 d and 7.5 d, respectively